Cost-effectiveness analysis of branded and authorized generic celecoxib for patients with chronic pain in Japan. - Yusuke Karasawa (Public Library of Science (PLoS), 2021)
Objectives The aim of this study was to examine the cost-effectiveness of branded and authorized generic (AG) celecoxib for chronic pain patients with osteoarthritis (OA), rheumatoid arthritis (RA), and low back pain (LBP), using real-world cost information for loxoprofen and pharmacotherapy for gastrointestinal bleeding. Methods This cost-effectiveness analysis was performed as a long-term simulation using the Markov model from the Japanese public healthcare payer's perspective. The analysis was conducted using loxoprofen with real-world weighted price by branded/generic distribution (hereinafter, loxoprofen with weighted price) as a comparator. In the model, we simulated the prognosis of patients with chronic pain by OA, RA, and LBP treated with loxoprofen or celecoxib, over a lifetime period. Results A cost-increase of 129,688 JPY (1,245.00 USD) for branded celecoxib and a cost-reduction of 6,268 JPY (60.17 USD) for AG celecoxib were recognized per patient in lifetime horizon, compared to loxoprofen with weighted price. No case was recognized to reverse the results of cost-saving by AG celecoxib in one-way sensitivity analysis. The incremental cost-effectiveness ratio of branded celecoxib attained 5,403,667 JPY/QALY (51,875.20 USD/QALY), compared to loxoprofen with the weighted price. Conclusion The current cost-effectiveness analysis for AG celecoxib revealed its good value for costs, considering the patients' future risk of gastrointestinal injury; also, the impact on costs due to AG celecoxib against loxoprofen will be small. It implies that the disadvantage of AG celecoxib being slightly more expensive than generic loxoprofen could be offset by the good cost-effectiveness during the prognosis.